Semiotic Analysis Of Coca-Cola Advertisement "Retro Grocery Store" Based On Charles Sanders Peirce's Theory Of Sign - Tiones Sagala; Nurul Khotimah; Mingga Ria Hadi; Asri Jannah Wati; Gloria Jersey Mozrapa; Peni Marcdianti; Mayang Pipit (International Journal of Technology and Education Research, 2026)
This aim for analyse meaning the signs contained in Coca-Cola themed advertisement Retro Grocery Store use approach Charles Sanders Peirce's semiotics. Advertisement the display life every day at a grocery store small with nostalgic nuances, combined with Coca-Cola's visual identity as global brands. Research use method study qualitative with approach descriptive and technical analysis Peirce's semiotics which includes representamen, objects, interpretants, and classification sign in the form of icons, indexes, and symbols. Research data in the form of visual scenes, expressions characters, layout, lighting, colour, properties, and audio-visual elements that appear in advertisement. Research results show that every visual element in advertisement no only functioning as marker products, but also build meaning cultural, social, emotional, and ideological. Representations include a grocery store, a retro- style Coca-Cola poster, a red lantern, a piggy bank, and lighting warm form object in the form of life public class medium, value family, culture local, as well as identity Coca-Cola brand. The resulting interpretation leading to meaning about nostalgia, warmth connection social, simplicity life, and closeness emotional between consumer with brand. The use of icons, indexes, and symbols strengthen Coca-Cola's image as part from experience daily public cross culture. Research show that Coca-Cola's visual communication strategy was successful integrate mark culture local with global identity through construction systematic signs​ so that capable create easy meaning​ accepted by the audience.